The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/jcbtp-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

How Does International Financial Integration Really Affect Post-Transition Countries' Growth? Empirical evidence from the CEE-10 countries

Abstract: This paper seeks to empirically explore how an international financial integration influences a country’s GDP growth. The long run relationship is tested by PMG estimator for the sample of ten EU countries from Central, Eastern and Southeastern Europe (CEE-10 countries) between 1995 and 2017. Prior to the conducting of dynamic panel analysis based on PMG estimators, several panel unit root tests were conducted, as well as panel co integration tests. The findings offer mixed impact financial integration on grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…They found that several factors, such as domestic credit, financial openness, and trade openness, have a statistically significant impact on the level of global financial integration in the GCC region. Ganić and Hrnjić (2021) examined the relationship between international financial integration and growth in ten Central and Eastern European (CEE) countries between 1995 and 2017. Their findings revealed a reversal relationship between growth and international financial integration, measured by Gross Foreign Assets and Liabilities to GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that several factors, such as domestic credit, financial openness, and trade openness, have a statistically significant impact on the level of global financial integration in the GCC region. Ganić and Hrnjić (2021) examined the relationship between international financial integration and growth in ten Central and Eastern European (CEE) countries between 1995 and 2017. Their findings revealed a reversal relationship between growth and international financial integration, measured by Gross Foreign Assets and Liabilities to GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of financial integration can be evaluated by using the IFI 1 indicator, which measures the ratio of a country's assets and liabilities to its GDP. This indicator is commonly used to gauge the level of financial integration and openness in a country, and has been used in various studies to assess financial integration (Vo & Daly, 2004;Bekaert et al, 2005;Ganić and Hrnjić, 2021). As capital flows become more fluid, international financial integration tends to improve.…”
Section: Defining Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganić's (2020a) study on financial integration in the Emerging Balkans highlighted the low and weak market capitalization of GDP in these countries, indicating underdevelopment and modest progress in financial integration. However, Ganić and Hrnjić (2021) explained in the study how International financial integration affects posttransition countries' growth. Through different empirical evidence, they concluded that when it comes to posttransition countries, there is no strong link between finance integration and growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gherghina, L.N. Simionescu, Oana S. Hudea (Gherghina et al, 2019), M. Ganić, M.Hrnjić (Ganić, 2021), B. Setiawan, A. Saleem, R. Jeyakumar Nathan, Z. Zeman, R. Magda and J. Barczi (Setiawan et al, 2021) and others.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%